(untitled) (Research, Society and Development, 2021)
There are few reports of regenerative endodontic procedures in molars, and most using manual root canal preparation. This case series describes a modified revascularization technique used in permanent molars (five patients between 9 and 16 years old). Patients were referred by an emergency service and a diagnostic hypothesis was made based on the patient’s reports. At the first appointment, coronal preparation was performed using Hedstroem files and Gates Glidden drills, followed by complete root canal preparation with rotary NiTi files. Calcium hydroxide (Ca(OH)2) paste was used as intracanal medication. At the second appointment, intracanal medication was removed, followed by final irrigation with EDTA under ultrasonic agitation, and the clot was promoted. The entrances of the canals were sealed using a mineral trioxide aggregate sealer (MTA) and provisionally restored with a light-cured glass ionomer. All teeth were finally restored using direct composite resin restoration and were followed for up to 18 months, checking pain, edema, and fistula during clinical evaluation. Radiographic examinations were performed to assess apical repair until 15 months, where root apex closure and canal reduction were observed. After 6 months, evidence of healing was observed in all cases. It was possible to confirm that endodontic regeneration after mechanized root canal preparation, use of a MTA sealer, and direct composite resin restoration in molars is a promising option for maintaining permanent molars in adolescents.